The landscape of paediatric in-hospital cardiac arrest in the United Kingdom National Cardiac Arrest Audit. (October 2020) - Skellett, Sophie; Orzechowska, Izabella; Thomas, Karen; Fortune, Peter-Marc
Abstract: Aim: To report the patient characteristics and clinical outcome of paediatric in-hospital cardiac arrest in the United Kingdom (UK) National Cardiac Arrest Audit (NCAA) database. Methods: Analysis of all recorded paediatric cardiac arrests in the NCAA dataset over a seven-year period ending on 31 December 2018, within acute children's hospitals (including standalone paediatric hospitals and hospitals with tertiary paediatric services) and acute general hospitals participating in NCAA. In this period 1456 patients (with 1580 events), 1 month to 16 years of age, received chest compressions and/or defibrillation and were attended by a hospital-based resuscitation team in response to an emergency call. The main outcome measure was survival to discharge. Results: For this cohort of paediatric in-hospital cardiac arrest patients the overall rates of sustained return of spontaneous circulation (ROSC) were 69.1% with unadjusted survival to hospital discharge of 54.2%. The presenting rhythm was shockable in 4.3% of events and non-shockable in 82.1% (remainder undetermined); rates of survival to hospital discharge associated with these rhythms were 63.9% and 51.7%. A difference in outcomes was observed between Children's hospitals and acute general hospitals with ROSC rates of 79.1% and 55.5% respectively and survival to hospital discharge rates of 57.7% and 49.3% respectively. Conclusions: These first results from the NCAA database describing the outcome of paediatric in-hospital cardiac arrest in UK hospitals will serve as a benchmark from which to assess the future impact of changes in service delivery, organisation and treatment for in-hospital cardiac arrest in young people. Outcomes for specialist paediatric centres should be studied further as higher rates of ROSC and survival to hospital discharge were observed.